The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsapm.2c00172
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible Polylactide Food Packaging Plasticized with Nontoxic, Biosourced Glycerol Plasticizers

Abstract: Polylactide (PLA) is a promising biosourced and biodegradable polymer substitute for traditional petroleum-based products. Despite its recognized potential, its widespread adoption is restricted by its brittleness and low ductility and, thus, to enhance its material properties, plasticizers must be blended with PLA to lower the glass transition temperature (T g) and impart flexibility into the blend. As such, this work focused on the synthesis of a family of biosourced plasticizers for applications in flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…In addition to evaluating the thermal and mechanical properties of the plasticizers in PVC blends, we aimed to investigate their toxicity through an in vitro mammalian cell assay. It was previously shown via an in vitro cytotoxicity assay that the glycerol compounds functionalized with linear chains of six carbons or less are nontoxic, whereas the longer chain or branched analogs showed mild levels of toxicity over a seven‐day period 32 . Here, we also evaluated two widely used phthalate‐based plasticizers for their cytotoxicity–di(2‐ethylhexyl) phthalate (DEHP) and DOTP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to evaluating the thermal and mechanical properties of the plasticizers in PVC blends, we aimed to investigate their toxicity through an in vitro mammalian cell assay. It was previously shown via an in vitro cytotoxicity assay that the glycerol compounds functionalized with linear chains of six carbons or less are nontoxic, whereas the longer chain or branched analogs showed mild levels of toxicity over a seven‐day period 32 . Here, we also evaluated two widely used phthalate‐based plasticizers for their cytotoxicity–di(2‐ethylhexyl) phthalate (DEHP) and DOTP.…”
Section: Resultsmentioning
confidence: 99%
“…The cell‐counting kit‐8 (CCK‐8) was purchased from Cedarlane Laboratories Ltd (Burlington, ON). The glycerol plasticizers used in this study were synthesized in accordance with a previously reported procedure 32 …”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations